Determining the Relationship of Acute Stress, Anxiety, and Salivary α-Amylase Level With Performance of Student Nurse Anesthetists During Human-Based Anesthesia Simulator Training. - McKay, Kelly A. Chiffer; Buen, John E.; Bohan, Kevin J.; Maye, John P. (AANA Journal, 2010)
Managing stress for student nurse anesthetists represents a multifaceted educational concern for anesthesia educators. Our purpose was to determine the relationship between physiologic measures of stress and performance of student nurse anesthetists during anesthesia simulator training. Following institutional review board approval, 18 students were enrolled from a nurse anesthesia program. A prospective descriptive design was used to compare baseline, acute, and recovery measurements of stress with performance scores of students during an induction and intubation sequence in a patient simulator. Performance scores were stratified into low-, moderate-, and high-performing groups based on scores received from trained observers. A statistically significant difference in physiologic measures of stress was detected between baseline and acute levels of salivary α-amylase (P = .017), heart rate (P = .003), and anxiety levels (P = .001). No significant differences were found when measures of stress were compared with performance of low, moderate, or high performers. This investigation revealed remarkable findings regarding the relationship between stress and student performance. Analysis of the descriptive statistics and means of each group suggests that low performers have increased stress and perform poorly, whereas high performers have increased stress and perform superbly, and moderate performers have modest stress and perform moderately.